An unusual presentation of compartment syndrome. Issue 5 (May 2015) - Martin, Cameron
<x xml:space="preserve">Abstract</x> ABSTRACT Compartment syndrome occurs when excessive pressure in an enclosed space in the body compromises perfusion. Without treatment, this condition can cause tissue ischemia and necrosis. Typically, acute compartment syndrome develops acutely after traumatic injury. The article describes a case of delayed compartment syndrome after a fall.